Ethics as a major element of sustainability in educational leadership across Finnish education - Ahmed, Qazi (2016)
The present study is an effort to analyze the concept of Ethics as a major element of sustainability in educational leadership across Finnish Education. It mainly involves with the elements such as ethical leadership and the notion of sustainability in Finnish educational leadership. The current research is mainly thematic discussion, and it discusses the above mentioned elements through qualitative method. In this respect, the present study rests on phenomenological approach, which has provided the researcher a better understanding of the phenomenon under investigation.The data was gathered from the principals and superintends working in different leadership roles in different cities of Finland. The present study has considerable findings, where it has brought out the facts that after analyzing the interviews, it is clear that ethical and sustainable leadership are of paramount significance. Similarly, trust, mutual collaboration and sense of mutual responsibilities are essential elements for the progress and positive outcome in educational institutes. The current research is of significant value, as it sheds light on the basic elements of educational leadership, because everything depends upon leadership. It leads the reader towards a new dimension, which is the essential relationship between ethics, sustainability and leadership. Moreover, where it reflects the characteristics of Finnish education system, it also provides guidelines to the international educationists in making their respective educational systems more progressive and systematic. Finally, the present study concludes that ethics plays a vital role in sustainability of educational leadership in Finnish education.